2022
DOI: 10.1101/2022.02.11.479668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omission responses in field potentials but not spikes in rat auditory cortex

Abstract: Non-invasive recordings of gross neural activity in humans often show responses to omitted stimuli in steady trains of identical stimuli. This has been taken as evidence for the neural coding of prediction or prediction error. However, evidence for such omission responses from invasive recordings of cellular-scale responses in animal models is scarce. Here, we sought to characterise omission responses using extracellular recordings in the auditory cortex of anaesthetised rats. We profiled omission responses ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Our null findings suggest a number of non-exclusive possibilities. First, it could be that omission responses are not robustly encoded in the widefield calcium activity (analyzed here) or spiking activity mainly from excitatory neurons in the superficial layers (to which wide-field imaging is most sensitive) (Waters, 2020), but rather in population activity (Auksztulewicz et al, 2022) potentially reflecting dendritic currents (Guerguiev et al, 2017), or in other types of neurons. This possibility is consistent with a recent calcium imaging study in the visual cortex, where neural activity following omissions was observed in L2/3 inhibitory neurons, but not in L2/3 excitatory neurons (Garrett et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our null findings suggest a number of non-exclusive possibilities. First, it could be that omission responses are not robustly encoded in the widefield calcium activity (analyzed here) or spiking activity mainly from excitatory neurons in the superficial layers (to which wide-field imaging is most sensitive) (Waters, 2020), but rather in population activity (Auksztulewicz et al, 2022) potentially reflecting dendritic currents (Guerguiev et al, 2017), or in other types of neurons. This possibility is consistent with a recent calcium imaging study in the visual cortex, where neural activity following omissions was observed in L2/3 inhibitory neurons, but not in L2/3 excitatory neurons (Garrett et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These include an auditory component capable of abstracting salient temporal patterns out of a complex acoustic signal [33,[51][52][53][54][55][56], a predictive component capable of projecting a pattern forward to predict the timing of future stimulus input [57][58][59][60][61][62], an auditory-motor connection capable of using sensory information and feedback to time motor actions in anticipation of future sound events [63][64][65][66], and the coordination of these through and association with reward that is either intrinsic or conditioned [37][38][39].…”
Section: Discussionmentioning
confidence: 99%

Monkeys have rhythm

Rajendran,
Marquez,
Prado
et al. 2024
Preprint
Self Cite
“…Such an architecture can reconcile predictive coding networks with the lack of strong evidence for there being explicit prediction error neurons in the cortex [11], unlike the dopaminergic reward prediction error neurons in the mid-brain whose existence has been established for decades [99, 100]. For example, a recent study in rat cortex found little evidence for prediction-related signals in spikes, but found strong evidence for it in local field potentials, which are thought to be driven by somatic and dendritic potentials [101]. Although in Fig 2B and C we still use error neurons in the hierarchical part of the network, they can also be circumvented following the dendritic implementation in [102].…”
Section: Discussionmentioning
confidence: 99%